High-Intensity Continuous Light from Red–Blue Light-Emitting Diodes Improved Yield, Nutritional Quality and Reactive Oxygen Species Accumulation in Two Leaf-Color Lettuces - Wenke Liu; Bing Liu; Qibao Wu (Biology)
In an environmentally controlled plant factory with LED red–blue light, the effects of conventional light (4R:1B, 200 μmol·m−2·s−1, 18/6 h) and continuous light (CL, 24/0 h) with three light intensities (4R:1B, 200, 300 and 400 μmol·m−2·s−1, 24/0 h) on yield, nutritional quality, reactive oxygen species (ROS) content and 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity (DPPH) in green-leaf Yidali and purple-leaf Zishan lettuces were investigated. The results showed that the dry and fresh shoot weight of two lettuces exposed to CL tended to increase with light intensity—from 200 to 400 μmol·m−2·s−1—compared to conventional light, while the leaf area tended to decrease or remained unchanged. High-intensity CL could significantly increase soluble sugar and reduce the nitrate contents of the two lettuces. Also, the antioxidant substance (anthocyanins, flavonoids and total phenols) content of the two lettuces was improved with the increase in CL intensity. High-intensity CL could significantly increase the malondialdehyde, hydrogen peroxide and superoxide anion content and DPPH of the two lettuces. The above indices showed similar results both at 6 and 12 days after light treatment. In contrast, the Zishan cultivar contained more antioxidant substances, ROS and MDA contents and DPPH (more than 1 to 100 times) than the Yidali cultivar under high-intensity CL. In summary, high-intensity CL could improve the yield and nutritional value of both Yidali and Zishan lettuces. The high CL tolerance of Zishan was attributed to a stronger antioxidant capacity due to a greater content of antioxidant substances and DPPH, while the accumulation of ROS and the content of antioxidant substances might interact.